2015
DOI: 10.4269/ajtmh.14-0402
|View full text |Cite
|
Sign up to set email alerts
|

Infectiousness of the Human Population to Anopheles arabiensis by Direct Skin Feeding in an Area Hypoendemic for Malaria in Senegal

Abstract: Abstract. Direct skin feeding experiments are sensitive assays to determine human infectiousness to mosquitoes but are rarely used in malaria epidemiological surveys. We determined the infectiousness of inhabitants of a malaria hypoendemic area in Senegal. Gametocyte prevalence by microscopy was 13.5% (26 of 192). Of all individuals who were gametocyte positive, 44.4% (11 of 25) infected 1 Anopheles arabiensis mosquito and 10.8% (54 of 500) of mosquitoes became infected. Of all individuals who were gametocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 27 publications
0
32
1
Order By: Relevance
“…The investigations were designed: (i) to compare direct and membrane feeding assays [10, 1519], (ii) to characterize infectious reservoirs [10, 11, 17, 2022], and/or (iii) to investigate transmission-interrupting activity [17, 18, 23]. The studies employed six Anopheline species/ sibling species and primarily targeted Plasmodium falciparum and vivax ; however, infections by P. malariae and P. ovale were also considered in five studies [10, 11, 16, 21, 22]. Study samples, which included between 15 and 685 participants, represented a wide range of ages (0.8 to 77 years); 7 of the studies restricted the cohorts to individuals who were gametocyte positive at the time of feeding.…”
Section: Direct Skin Feeding Assays To Measure Malaria Transmissiomentioning
confidence: 99%
See 1 more Smart Citation
“…The investigations were designed: (i) to compare direct and membrane feeding assays [10, 1519], (ii) to characterize infectious reservoirs [10, 11, 17, 2022], and/or (iii) to investigate transmission-interrupting activity [17, 18, 23]. The studies employed six Anopheline species/ sibling species and primarily targeted Plasmodium falciparum and vivax ; however, infections by P. malariae and P. ovale were also considered in five studies [10, 11, 16, 21, 22]. Study samples, which included between 15 and 685 participants, represented a wide range of ages (0.8 to 77 years); 7 of the studies restricted the cohorts to individuals who were gametocyte positive at the time of feeding.…”
Section: Direct Skin Feeding Assays To Measure Malaria Transmissiomentioning
confidence: 99%
“…Differences between study groups (e.g. age categories) were most frequently evaluated using non-parametric approaches [11, 1517, 19, 21, 22]; however, several studies – and, notably, two investigating transmission-interrupting activity – reported qualitative differences alone [18, 20, 23]. Diallo, et al (2008) compared mean oocyst prevalence with a student’s t-test [10].…”
Section: Direct Skin Feeding Assays To Measure Malaria Transmissiomentioning
confidence: 99%
“…Unlike vaccines that aim to protect high risk groups from (severe) disease, SSM-VIMT aim for high coverage in the entirety of the human population that contributes to malaria transmission. This reservoir comprises all age groups [63,83]. SSM-VIMT application will in a way resemble mass drug administration campaigns for which high coverage over repeated rounds has been shown to be a considerable challenge [84,85].…”
Section: Public Health Impact Of Ssm-vimtmentioning
confidence: 99%
“…This Phase 3 trial will involve a cluster-randomized design and outcome measures based on PCR-detected infection incidence with clinical endpoints and safety evaluations as secondary objectives. The assumptions, outcome and design of a cluster randomized trial for SSM-VIMT were recently reported as outcome of a series of expert meetings [83]. The power and require sample size strongly depend on the chosen settings and their characteristics in terms of transmission intensity (ideally intermediate intensity transmission; ∼0.6 incident infections/person/year), stability of transmission, other malaria interventions, homogeneity of transmission between clusters and migration of unvaccinated individuals into intervention areas.…”
Section: Cluster-randomized Trials For Public Health Endpointsmentioning
confidence: 99%
“…These then migrate to the salivary glands and are transferred by saliva into the skin of the next individual the mosquito bites. The majority of sporozoites released into the host stay in the dermal layer, at the site of entry, and do not contribute to infection [9][10][11][12] . However, approximately 35% of injected parasites migrate away from the site of infection via the lymphatics or the blood.…”
Section: Parasite Life Cyclementioning
confidence: 99%